2015
DOI: 10.1002/jms.3721
|View full text |Cite
|
Sign up to set email alerts
|

A semi‐quantitative approach for the rapid screening and mass profiling of naphthenic acids directly in contaminated aqueous samples

Abstract: We report the use of a direct sampling, online analytical approach for the determination of acid extractable naphthenic acids in complex aqueous samples, known as condensed phase membrane introduction mass spectrometry (CP-MIMS). The technique employs a capillary hollow fibre semi-permeable membrane probe configured for immersion into a pH adjusted sample. A continuously flowing methanol acceptor phase transfers naphthenic acids to an electrospray ionization source, operated in negative ion mode, whereupon the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 29 publications
4
36
0
Order By: Relevance
“…Condensed-phase membrane introduction mass spectrometry (CP-MIMS) is a rapid screening method, which has been employed to directly measure aqueous NAs and PAHs in situ (Duncan et al, 2016a;Termopoli et al, 2016;Vandergrift et al, 2019). The technique uses a semipermeable hollow fiber membrane (typically polydimethylsiloxane), which is directly immersed into a liquid or slurry sample.…”
Section: Introductionmentioning
confidence: 99%
“…Condensed-phase membrane introduction mass spectrometry (CP-MIMS) is a rapid screening method, which has been employed to directly measure aqueous NAs and PAHs in situ (Duncan et al, 2016a;Termopoli et al, 2016;Vandergrift et al, 2019). The technique uses a semipermeable hollow fiber membrane (typically polydimethylsiloxane), which is directly immersed into a liquid or slurry sample.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the product ions are common for . We have previously demonstrated CP-MIMS as a potential rapid screening methodology for naphthenic acids from contaminated aqueous samples [20,24]. Further, recent work has shown that hydroxylated compounds contribute signal to CP-MIMS quantification of NAs using negative ion ESI (data not shown).…”
Section: Non-targeted Tandem Ms Screening Of Naphthenic Acidsmentioning
confidence: 97%
“…(B) Aniline (~70 ppb), which is present initially as the anilinium ion in acidic solution, is titrated to the neutral aniline form as the pH increases. selected ion monitoring in negative ion mode with a cone voltage of 30 V. The membrane-permeable naphthenic acid fraction that readily ionizes in negative ion ESI displays approximately 100 observable peaks between m/z 150 and 350 at unit mass resolution (Duncan et al 2016). Selecting the 30 most abundant m/z values, we monitored the changes in their relative signal chronogram intensities as a function of the sample pH to generate apparent pK a values for given isomer classes.…”
Section: Naphthenic Acidsmentioning
confidence: 99%
“…Because the neutral form of the carboxylic acids are titrated out in the sample, the neutral alcohols continue to permeate and their ionization is no longer suppressed by the presence of carboxylic acids in the ESI (Letourneau 2016). Whereas the nominal mass resolution of the experiments we describe limits our ability to ascribe exact molecular formulas, higher resolution mass analyzers, such as the Fourier transform ion cyclotron resonance and Orbitraps, have been successfully coupled to membrane interfaces to provide molecular formula information (Duncan et al 2016). The ability to simultaneously determine multiple acidity constants in a complex mixture containing only trace amounts of individual compounds, is a clear advantage of the technique.…”
Section: Naphthenic Acidsmentioning
confidence: 99%